Chlorine activation within urban or power plant plumes: Vertically resolved ClNO2 and Cl2 measurements from a tall tower in a polluted continental setting. Issue 15 (15th August 2013) - Riedel, Theran P.; Wagner, Nicholas L.; Dubé, William P.; Middlebrook, Ann M.; Young, Cora J.; Öztürk, Fatma; Bahreini, Roya; VandenBoer, Trevor C.; Wolfe, Daniel E.; Williams, Eric J.; Roberts, James M.; Brown, Steven S.; et al.
Abstract: [1] Nitryl chloride (ClNO2 ) is a chlorine atom source and reactive nitrogen reservoir formed during the night by heterogeneous reactions of dinitrogen pentoxide on chloride‐containing aerosol particles. The main factors that influence ClNO2 production include nitrogen oxides, ozone, aerosol surface area, soluble chloride, and ambient relative humidity. Regions with strong anthropogenic activity therefore have large ClNO2 formation potential even inland of coastal regions due to transport or local emissions of soluble chloride. As part of the Nitrogen, Aerosol Composition, and Halogens on a Tall Tower field study, we report wintertime vertically resolved ClNO2 and molecular chlorine (Cl2 ) measurements taken on a 300 m tall tower located at NOAA's Boulder Atmospheric Observatory in Weld County, CO, during February and March of 2011. Gas and particle phase measurements aboard the tower carriage allowed for a detailed description of the chemical state of the nocturnal atmosphere as a function of height. These observations show significant vertical structure in ClNO2 and Cl2 mixing ratios that undergo dynamic changes over the course of a night. Using these measurements, we focus on two distinct combustion plume events where ClNO2 mixing ratios reached 600 and 1300 parts per trillion by volume, respectively, aloft of the nocturnal surface layer. We infer ClNO2 yields from N2 O5 ‐aerosol reactions using both observational constraints and box modeling. The derived yields in these plumes suggest efficient ClNO2 production compared to the campaign average, where in‐plume yields range from 0.3 to 1; the campaign average yield in the boundary layer is 0.05 ± 0.15, with substantial night‐to‐night and within night variability similar to previous measurements in this region. Key Points: Vertical measurements of ClNO2 and Cl2 show large variability with height. ClNO2 is enhanced in air only from polluted sectors. Evidence for ClNO2 and Cl2 production/emission from local combustion sources.